Thermal performance and heat dissipation analysis of hybrid nanofluids in microchannel heat sinks using Yamada-Ota and Hamilton-Crosser models - Muhammad Adil Sadiq; Ishak Bin Hashim (Journal of Taibah University for Science)
This manuscript investigates the dynamics of a hybrid nanofluid based on the Yamada-Ota and Hamilton-Crosser models, comprising copper, titanium oxide, and aluminium oxide with a blood base fluid. The hybrid nanofluid, applied to sensor surfaces modeled as two parallel plates using Darcy-Forchheimer theory, enhances cooling in microchannel heat sinks. This approach improves heat dissipation and sensor reliability under high thermal loads. The study analyzes the impact of the hybrid nanofluid on heat transfer and skin friction coefficients, incorporating effects like Joule heating, heat sink, thermal diffusion, and Dufour's effect. Governing equations are transformed into ODEs and solved numerically using the finite element method via MAPLE 18, noted for its accuracy and adaptability. The model presents a novel application, as such a configuration has not yet been explored using FEM. The results reveal superior thermal transfer characteristics of hybrid nanofluids over standard nanofluids, with reduced heat energy production, thus confirming the model's novelty and significance in thermal management.